A prospective solution For consistent aerostatic lift for a hybrid buoyant aircraft - Haque, Anwar Ul; Asrar, Waqar; Sulaeman, Erwin; Mohamed Ali, Jaffar Syed; Omar, Ashraf Ali (IEOM Society, 2016)
Concept of aerostatic lift from the long ignored buoyant aerial vehicles has now a day been applied for partial fulfilment of the lift requirement for hybrid buoyant aircraft. This diffused lift technology seems to have eradicated the separate requirement of the heating mechanism for the lifting gas. In comparison with conventional aircraft, such aircraft have big surface area available on the voluminous fuselage which is made up of thin shells and transverse frames. Depending on the power requirement and the power available through the irradiance modeling, partial surface area of fuselage can be utilized to provide power to the miniaturized avionics, specially the electrically driven heating elements; a prospective solution to provide heat to the lifting gas on as and when required basis. Potential issues related to the heat generated by the solar cells, bulky batteries and fuel powered plasmatrons are also discussed. A methodology for system design for the said issue is proposed. Based on the irradiance model of Malaysia, solar energy available throughout the day has been calculated. A detailed analysis is required for accurate estimation of energy and power budget along with a fine balance between the heat available and the one required. © IEOM Society International.